Challenges in Intellectualizing Sesotho for Use in Academic Publications - Johannes Sibeko; Mmasibidi Setaka (Journal of Electronic Publishing)
This paper explores challenges in intellectualizing Sesotho for academic works beyond literary-based theses. It also overviews resources for the intellectualization of official Indigenous languages of South Africa, focusing on national translation projects for terminology development. Furthermore, it highlights efforts by the South African Centre for Digital Language Resources in creating and collecting corpora for all official languages, including Sesotho. Challenges in Sesotho lexicography, especially with corpus-based approaches, are discussed. Additionally, the paper reflects on the authors' experiences with publishing academic articles in Sesotho in South African journals. It discusses obstacles faced, and strategies employed, including dialogues with reviewers on creating new terms and choosing between Lesothan Sesotho and South African Sesotho orthographies. Finally, the essay addresses challenges posed by limited publication avenues for indigenous languages in southern Africa and academic pressures for citations and research impact. It aims to shed light on lesser-known Indigenous languages in Southern Africa by spotlighting challenges and solutions to academic publications in Sesotho. Overall, the paper concludes that efforts at intellectualizing Sesotho and other South African indigenous languages are evident. Even so, there is far less emphasis on using Sesotho and other indigenous languages for academic discourses.